Über die Kriterien bei und die Zufriedenheit mit der Wahl eines Master-Studiengangs: Am Beispiel der agrarwissenschaftlichen Master-Studiengänge der Justus-Liebig-Universität Gießen; Assessing the Criteria for and the Satisfaction with the Choice of a Graduate School: an Example from the Master Courses in Agriculture at the University of Giessen - Andreas Hildenbrand; Soviana Soviana (German Journal of Agricultural Economics (GJAE), 2015)
– The knowledge of relevant criteria and important motives for the choice of a course can help a university in improving present courses and developing future courses. This knowledge will enable a university to strategically increase its attractiveness for actual and potential students. Whereas the undergraduate school choice is explored to a large extent, the graduate school choice is largely unexplored. We analyze the master courses in agriculture at the University of Giessen by conducting a survey. We use marketing research methods to analyze our survey data.
Keywords: 330